(untitled) ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
This article explores cognitive listening strategies for language learners, emphasizing techniques that enhance comprehension and listening skills. It introduces strategies such as predicting content, chunking information, identifying key words, inferring meaning from context, and making connections to prior knowledge. The article also highlights the importance of active listening, repetition, and self-reflection in improving listening abilities. By integrating these strategies, learners can more effectively process spoken language, overcome challenges, and increase their confidence in understanding both everyday conversations and academic content. Overall, the article serves as a practical guide for language learners looking to sharpen their listening skills through cognitive approaches.